Investigating metacarpi of Hamdani sheep via different measurement and modelling methods: A methodological study - Guzel, Baris Can; Kocyigit, Ali; Demircioglu, Ismail; Demiraslan, Yasin (Wiley, 2022)
The aim of the study was to perform the morphometric analyses on metacarpi of Hamdani sheep via different measurement methods and to compare the methods. Thus, metacarpal bones of 15 females and 15 males were used in the study. Measurements were taken from the measurement points determined on metacarpus via four methods, and their statistical analyses were performed. When both male and female metacarpal bones were examined in the De parameter in the comparison with the methods, it was observed that the four measurement methods were different from one another (p < 0.01). When DEM and DEL measurement parameters were examined in male metacarpus, the highest value was measured in ImageJ and the smallest value was measured in 3D Slicer software; however, it was found that the statistical difference was not significant when compared numerically (p > 0.05). As a result, while it was observed that the measurements made by using digital calliper measurements, photometric analysis, and 3D software were similar in some of the parameters but there was no statistically significant difference; whereas, Statistical difference was detected in some parameters.
Keywords: Hamdani sheep; metacarpus; methodology; morphometry